Spectroscopic and dielectric characteristics of nickel-doped porous silica glasses - Macalik, Bogusław; Suszyńska, Maria; Rysiakiewicz-Pasek, Ewa; Krawczyk, Ludwina; Morawska-Kowal, Teresa; Okal, Janina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The direct current conduction and electrical relaxation currents in nickel-doped porous silica glasses were investigated by using the thermally stimulated polarisation and depolarisation current techniques in a wide temperature range. Optical absorption measurements and transmission electron microscopy observations accompanied these studies. All characteristics were found to be affected by the porous matrix and the material filling the pores.
Optica Applicata, Vol. 35, 2005, nr 4, s. 761-767
Keywords: optyka; nickel nanoparticles; porous glasses dielectric properties; optical absorption